THE INFLUENCE OF WORK-LIFE CONFLICT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH EMPLOYEE WELFARE AS A MEDIATION VARIABLE - Anggi Putri Susiana; Sutarmin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The phenomenon of a gap in employee performance decline indicates that the work achievements produced are not fully in accordance with organizational standards and expectations. Therefore, the purpose of this study is to examine and analyze the influence of work-life conflict and organizational culture on employee performance mediated by employee welfare variables. This research method uses a quantitative approach with a sample collection technique using probability sampling with a random sampling method. The research data were collected by distributing questionnaires to 200 respondents. The results of the analysis state that: 1) work-life conflict does not affect employee performance, 2) organizational culture has a positive effect on employee performance, 3) work-life conflict has a positive effect on employee welfare, 4) organizational culture has a positive effect on employee welfare, 5) employee welfare does not affect employee performance, 6) employee welfare is unable to mediate the influence of work-life conflict on employee performance, 7) employee welfare is unable to mediate the influence of organizational culture on employee performance.